Expanding spectrum of opportunistic infections associated with dimethyl fumarate. (July 2021) - Kim, Tiffany; Croteau, David; Brinker, Allen; Jones, David E; Lee, Paul R; Kortepeter, Cindy M
Background: Only progressive multifocal leukoencephalopathy (PML) is currently described in the dimethyl fumarate (DMF) prescribing information. Objectives: To describe opportunistic infections (OIs), other than PML, reported in association with DMF. Methods: The FDA Adverse Event Reporting System (FAERS) and medical literature were searched. Results: We retrieved 34 cases of serious OIs with a causal association with DMF, including 11 central nervous system (CNS) infections and 23 extra-CNS infections. Six OIs occurred with normal circulating absolute lymphocyte counts. The median latency from DMF initiation was 13 months and was variable. Conclusion: DMF is associated with the development of OIs that require invasive diagnostic and/or therapeutic procedures. Patients should be monitored for OIs when treated with DMF regardless of circulating absolute lymphocyte counts.